1995
DOI: 10.1007/bf01705530
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of two forms of Choline kinase and separation of Choline kinase from sphingosine kinase of rat brain

Abstract: Choline kinase of rat brain was purified approximately 200,000 fold using acid precipitation, ammonium sulphate fractionation, Q-Sepharose, Octyl-Sepharose and AH-Sepharose chromatography. The ability of this enzyme to catalyze the phosphorylation of choline, ethanolamine (Etn), monomethylethanolamine (MeEtn), dimethylethanolamine (Me2Etn) and sphingosine was investigated. Choline kinase was separated from sphingosine kinase. The fraction with highly purified choline kinase had four major polypeptides with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…We found that sphingosine kinase binds tightly to 1,6-diaminohexane covalently linked to Sepharose 4B (EAHSepharose), but could not be eluted from this matrix by substrates containing primary amino groups, such as sphingosine or choline, in a similar manner, as was previously found for purification of choline kinase (44). In contrast, at least 70% of the applied sphingosine kinase activity was eluted from EAHSepharose with 0.15 M NaCl, whereas only 14 -18% of the applied proteins were eluted in this fraction, resulting in 3-5-fold purification (Fig.…”
Section: Fig 4 Purification Of Sphingosine Kinase By Hydroxylapatitsupporting
confidence: 61%
See 1 more Smart Citation
“…We found that sphingosine kinase binds tightly to 1,6-diaminohexane covalently linked to Sepharose 4B (EAHSepharose), but could not be eluted from this matrix by substrates containing primary amino groups, such as sphingosine or choline, in a similar manner, as was previously found for purification of choline kinase (44). In contrast, at least 70% of the applied sphingosine kinase activity was eluted from EAHSepharose with 0.15 M NaCl, whereas only 14 -18% of the applied proteins were eluted in this fraction, resulting in 3-5-fold purification (Fig.…”
Section: Fig 4 Purification Of Sphingosine Kinase By Hydroxylapatitsupporting
confidence: 61%
“…Similarly, another kinase, choline kinase, has been partially purified from rat kidney by Ͼ200,000-fold (44). This study provides the basis for molecular characterization of sphingosine kinase and will aid in elucidation of its role in various physiological processes.…”
Section: Fig 4 Purification Of Sphingosine Kinase By Hydroxylapatitmentioning
confidence: 98%
“…versibility: ? <13>[15,27,41])[15,27,41] P ADP + N-methylethanolamine phosphate S N-monoethylethanolamine + ATP <20> (Reversibility: ? <20>[7])[7] P p-chloromercuribenzoate <19> (<5> no effect…”
mentioning
confidence: 99%